Size-resolved, quantitative evaluation of the magnetic mineralogy of airborne brake-wear particulate emissions - Gonet, Tomasz; Maher, Barbara A; Nyirő-Kósa, Ilona; Pósfai, Mihály; Vaculík, Miroslav; Kukutschová, Jana (Environmental pollution (Barking, Essex, 2021)
Exposure to particulate air pollution has been associated with a variety of respiratory, cardiovascular and neurological problems, resulting in increased morbidity and mortality worldwide. Brake-wear emissions are one of the major sources of metal-rich airborne particulate pollution in roadside environments. Of potentially bioreactive metals, Fe (especially in its ferrous form, Fe2+) might play a specific role in both neurological and cardiovascular impairments. Here, we collected brake-wear particulate emissions using a full-scale brake dynamometer, and used a combination of magnetic measurements and electron microscopy to make quantitative evaluation of the magnetic composition and particle size of airborne emissions originating from passenger car brake systems. Our results show that the concentrations of Fe-rich magnetic grains in airborne brake-wear emissions are very high (i.e., ~100-10,000 × higher), compared to other types of particulate pollutants produced in most urban environments. From magnetic component analysis, the average magnetite mass concentration in total PM10 of brake emissions is ~20.2 wt% and metallic Fe ~1.6 wt%. Most brake-wear airborne particles (>99 % of particle number concentration) are smaller than 200 nm. Using low-temperature magnetic measurements, we observed a strong superparamagnetic signal (indicative of ultrafine magnetic particles, < ~30 nm) for all of the analysed size fractions of airborne brake-wear particles. Transmission electron microscopy independently shows that even the larger size fractions of airborne brake-wear emissions dominantly comprise agglomerates of ultrafine (<100 nm) particles (UFPs). Such UFPs likely pose a threat to neuronal and cardiovascular health after inhalation and/or ingestion. The observed abundance of ultrafine magnetite particles (estimated to constitute ~7.6 wt% of PM0.2) might be especially hazardous to the brain, contributing both to microglial inflammatory action and excess generation of reactive oxygen species.
Keywords: znečištění ovzduší; Air Pollution; Magnetite; Magnetic Phenomena; Particulate matter; monitorování životního prostředí; Air Pollutants; velikost částic; Particulate Matter; pevné částice; látky znečišťující vzduch; magnetické jevy; Environmental Monitoring; Neurodegeneration; Particle Size; Air pollution; Vehicle Emissions; Brake wear; výfukové emise vozidel